Anne of windy willows - Montgomery, L. M. (Puffin London, 1994)
'Anne starts her new job as Principal of Summerside High School, but now she faces a new challenge: the Pringles. Summerside is virtually ruled by the large Pringle family, who make it quite clear they don't want Anne at the school.'--Back cover